2001
DOI: 10.1002/1521-379x(200112)53:12<605::aid-star605>3.0.co;2-u
|View full text |Cite
|
Sign up to set email alerts
|

Low- and Medium-DE Maltodextrins From Waxy Wheat Starch: Preparation and Properties

Abstract: Maltodextrin (MD) in the USA is a starch-hydrolysis product with a dextrose equivalent (D.E.) of less than 20 [1, 2]. MD's are widely used in fat mimetics, beverages, flavor carriers, frozen desserts, and nutritional products, to name a few. To date MD's from wheat starch have not been commercialized in the USA.Mainly, MD's are classified by DE, which is equal to 100 divided by the number-average degree of polymerization ( _ D _ _ P _ n ) of a MD. Increasing the DE of MD's increases their hygroscopicity, water… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
4
0

Year Published

2006
2006
2024
2024

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 13 publications
(5 citation statements)
references
References 30 publications
1
4
0
Order By: Relevance
“…Subsequently, the storage modulus was used to calculate the density of polymer chains per volume unit (ʋ e R ), according to Equation (4). Higher ʋe R values were observed for GLU_TTE in comparison with GLU_BDE, with values equal to 2.83 × 10 −6 ± 1.86 × 10 −6 mol/cm 3 and 2.38 × 10 −6 ± 9.68 × 10 −7 mol/cm 3 , respectively, which is in agreement with the results obtained from WAC and cross-linking density via the Flory-Rehner theory. This aspect can be explained by the presence, in the case of GLU_TTE, of a more cross-linked and compact network that is favored by employing a tri-functional cross-linker during the polymer synthesis.…”
Section: Rheological Measurementssupporting
confidence: 88%
See 1 more Smart Citation
“…Subsequently, the storage modulus was used to calculate the density of polymer chains per volume unit (ʋ e R ), according to Equation (4). Higher ʋe R values were observed for GLU_TTE in comparison with GLU_BDE, with values equal to 2.83 × 10 −6 ± 1.86 × 10 −6 mol/cm 3 and 2.38 × 10 −6 ± 9.68 × 10 −7 mol/cm 3 , respectively, which is in agreement with the results obtained from WAC and cross-linking density via the Flory-Rehner theory. This aspect can be explained by the presence, in the case of GLU_TTE, of a more cross-linked and compact network that is favored by employing a tri-functional cross-linker during the polymer synthesis.…”
Section: Rheological Measurementssupporting
confidence: 88%
“…This value represents the reducing equivalent of maltodextrin against the same mass of glucose. Usually, the higher the dextrose equivalent, the lower the molecular weight of the maltodextrin [3,4]. Because of maltodextrins' good water solubility, numerous studies reported the possibility of cross-linking them into insoluble polymer networks by exploiting suitable cross-linkers, aiming for application in aqueous media [5][6][7][8][9][10].…”
Section: Introductionmentioning
confidence: 99%
“…Maltodextrin (MDX) is a polysaccharide derived from starch hydrolysis and its main application is in the food industry as an artificial sweetener [27]. It is also used in agriculture as a constituent in some insecticides and acaricides [28]. It has been shown that NPs' morphology affects their optical, electrochemical, sensory, thermal and mechanical properties.…”
Section: Introductionmentioning
confidence: 99%
“…Cross-linking waxy wheat starch, akin to cross-linked waxy corn starch, imparts high and stable viscosity to processed foods (Reddy & Seib, 2000). Maltodextrins with dextrose equivalents of 1 and 10 were successfully produced from waxy wheat starches because of their lower levels (<0.1%) of lipids (Lumdubwong & Seib, 2001).…”
Section: Introductionmentioning
confidence: 99%